ANALISIS POTENSI DAN TINGKAT PERKEMBANGAN DESA DI KABUPATEN SUMENEP - Nurdody Zakki; Isdiantoni ,; Isnani Yuli Andini (Fakultas Ekonomi dan Bisnis, 2017)
Potential Data Village / kelurahan used to determine the level of general potential, development potential and typology of the village. The data is used as a reference for the Village Medium Term Development Plan (RPJMDes), investment and business development of the community, while the Village Development Rate Data is used to determine the rate of development of the village / kelurahan. The analysis of the rate of development of the village / kelurahan is used to determine the classification of the village / kelurahan (Swasembada, Swakarya and Swadaya) and the progress status of the village / kelurahan category of Mula, Madya dan lanjut. So it can be seen the value of community economic index, public education index, public health index, public participation index, security and order index, community participation index in development and development index of village / kelurahan. Objectives The formulation and empowerment of village / kelurahan profiles to provide relevant and valid primary data and information as reference for planning and implementation of development and empowerment of village / kelurahan community. The scope of this research was conducted in Errabu Village and Sera Tengah Village, Bluto Sub-District, Sumenep Regency. The method of this research is secondary data and primary data through observation process, interview (FGD), and Kuisioner from basic family data based on Directive of General Director of Community Empowerment and Village Kemendagri. The results of this study are for the classification of the annual development level of the two villages based on the results of the analysis of the indicators in the preparation of village profiles generated data with Category